2015
DOI: 10.1021/acs.energyfuels.5b01675
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of the Plain and Additized Mineral Base Oil Samples Monitored through Gas Chromatography–Mass Spectrometry

Abstract: Gas chromatography–mass spectrometry (GC–MS) was used to monitor the thermo-oxidative degradation of the plain and additized mineral base oil (MBO) samples. Antioxidants used were MeOH extracts of the rice husk (RHE) and saw dust (SDE). The oxidation was performed for 6 h at 200 °C according to the modified Institute of Petroleum (IP) method. The results indicate that the additized MBO samples inhibited thermo-oxidation compared to the plain sample. Among the two antioxidants, the RHE showed excellent antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…An initial increase in the number of HC [H] species at 24 h was also observed, however, because of the formation of new hydrocarbon species. Formation of new aliphatic and aromatic species has been observed previously, 24 and it is possible such species are formed from the alkylation of hydrocarbon species by an alkyl radical 53 occurring during the initial stages of oxidation.…”
Section: For Example C 32 H 60 O 4 [H] Is Part Of the Class O 4 [H] W...mentioning
confidence: 62%
See 2 more Smart Citations
“…An initial increase in the number of HC [H] species at 24 h was also observed, however, because of the formation of new hydrocarbon species. Formation of new aliphatic and aromatic species has been observed previously, 24 and it is possible such species are formed from the alkylation of hydrocarbon species by an alkyl radical 53 occurring during the initial stages of oxidation.…”
Section: For Example C 32 H 60 O 4 [H] Is Part Of the Class O 4 [H] W...mentioning
confidence: 62%
“…We can observe the effect of processes that increase the carbon number of the molecule via mass spectrometry by investigating the changes in the carbon number ranges observed; however, it is not possible to determine whether species have a linear or branched structure with direct infusion mass spectrometry alone. Additional techniques such as gas chromatography (GC) ,, or two-dimensional mass spectrometry would have to be employed to provide further insight into the structural arrangement of the carbon skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical compositions of the RHE and SDE were investigated by GC-MS analysis, which indicated that the antioxidants contained a variety of compounds including dihydroxy benzene, pyrogallol, alkylated phenols (anisols) and aromatic amines, hydro-quinone, naphtho-quinone, hydroxy benzoic acid, hydroxyquinoline, carboxylatedfuranone, hydroxybenzaldehyde, alkylated hydroxyl coumarine, naphthol, aromatic amines or amides, ascorbic acid, stearic acid, and tocopherols. 38 The original RHE and SDE were also characterized by FT-IR, the spectra are shown in Fig. 3(a) and (b) while the corresponding data is compiled in Tables 1 and 2.…”
Section: Original Rhe and Sdementioning
confidence: 99%
“…It is well-known that the oxidative degradation is one of the most important quality characteristics involved in the drain intervals of lubricating oil. This process is usually accompanied by the depletion of additives and degradation of base oils, during which undesirable polar oxidation products are formed, such as aldehydes, ketones, carboxylic acids, and polymers (ester, resin, and asphaltene). , These newly formed degradation products could lead to a gradual change of the physicochemical properties of the lubricating oil, viz., the decrease of total base number (TBN) could be observed in the initial stage of oxidative degradation, followed by the increase of total acid number (TAN) when additives were depleted and insufficient to neutralize the acidic products, and, lastly, the highly oxidized polymers and sludges could lead to a dramatically increase of kinematic viscosity (KV) and insoluble contents (IC). These properties are often assessed according to standard test methods such as ASTM D974 (for TAN), D445 (for KV), and D893 (for IC).…”
Section: Introductionmentioning
confidence: 99%